Improving the quality of mobile phone customer care service at Telecommunications Service Corporation - VNPT VinaPhone = Nâng cao chất lượng dịch vụ chăm sóc khách hàng thuê bao di động tại tổng công ty dịch vụ viễn thông VNPT Vinaphone - Phạm, Thị Thủy (2020)
Aims of researchThe thesis studies the basic arguments on service quality in general and the quality of customer service in the field of Telecommunications and mobile information in particular with the following objectives:Systematize some basic arguments about service quality, especially quality of customer care in the field of Telecommunications.The concept of customer careCriteria for evaluating customer service qualityFactors affecting customer service quality improvementAnalyze the status of customer service quality of VNPT VinaPhoneProposing solutions toimprove the quality of customer care services of VNPT VinaPhone